Programmatic Assessment: New Approach of Student Assessment in Medical Education of the Current Century - Hamid Mahdavifard (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Letter to the Editor Over the past few decades, education programs in health professions have moved toward a competency-based paradigm throughout the world. Competency-based education (CBE) relies on the fundamental principle that predetermined outcomes (competencies) guide teaching, learning, and assessment to ensure that graduates demonstrate proficiency in key competency domains and are able to provide care for patients with high quality throughout their careers. The purpose of CBE is to transform learners into healthcare workers who have lifelong learning and are committed to professional excellence, and the necessary competencies have been created in them. In CBE, learners are usually the center of attention and are actively involved in the learning and assessment process. Providing frequent and meaningful performance feedback enables learners to shape their learning paths by identifying appropriate learning opportunities for further development. Assessment is critical in achieving the goals of CBE. However, traditional approaches to assessment, which generally focus exclusively on the summative function of assessment, are not appropriate in CBE. Assessment programs should not only ensure robust decision-making about the progress and development of learners' competence but also facilitate the production of high-quality feedback for learning and support reflective practice and the use of feedback. Therefore, to continuously improve performance in CBE, assessment programs and assessment functions should be combined and integrated for learning. Programmatic assessment is a comprehensive approach in the assessment system that is theoretically aligned with key principles of CBE, as it aims to optimize assessment for learning while ensuring informed decision-making about learners' achievement of intended outcomes. In programmatic assessment, low-stakes assessments are continuously and purposefully considered to provide meaningful feedback on the longitudinal performance of learners to develop their competencies, while high-stakes assessments are based on the meaningful aggregation of data from multiple low-stakes assessments, which are collected over longer periods of time, at different periods in different contexts, and with multiple raters. However, while programmatic assessment approaches are increasingly being accepted as essential tools in the effective implementation of CBE, various research findings have indicated that it is difficult to merge different assessment performances in programmatic assessment. Performing programmatic assessment requires a change not only in assessment design but also in instructors and learners' views and data about objective and high-quality evaluation performance. Therefore, changing the assessment culture and fundamental data is necessary. Capacity building is a key element in any change process. All stakeholders involved in programmatic assessment must develop the capabilities needed to bring about the desired change in assessment culture. However, research findings suggest that stakeholders may not always be willing or able to perform the new roles as intended for them; instead, old behaviors "simply" adapt to new environments.